2000
DOI: 10.2214/ajr.174.5.1741363
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral Marrow Changes After Laser Diskectomy in the Lumbar Spine

Abstract: Subchondral marrow abnormalities may occur in the vertebral end plates after holmium:yttrium aluminum garnet laser diskectomy. However, these changes probably do not affect surgical outcomes and appear to resolve over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
4
16
0
1
Order By: Relevance
“…Grönemeyer et al reported the success rate of percutaneous laser discectomies (PLDDs) as 74% in 20 patients with HNP after a follow-up of 4 years (16). Although the results were similar to those of our present study, it has been shown that percutaneous laser nucleolysis offers an insufficient level of temperature control, which may lead to injury of adjacent tissues (17)(18)(19). This procedure comes with some disadvantages, such as moderate to severe intraoperative pain, thermal effects of the laser, postoperative back pain, spasm, and lack of visualization of the laser tip under fluoroscopy (20).…”
Section: Discussionsupporting
confidence: 87%
“…Grönemeyer et al reported the success rate of percutaneous laser discectomies (PLDDs) as 74% in 20 patients with HNP after a follow-up of 4 years (16). Although the results were similar to those of our present study, it has been shown that percutaneous laser nucleolysis offers an insufficient level of temperature control, which may lead to injury of adjacent tissues (17)(18)(19). This procedure comes with some disadvantages, such as moderate to severe intraoperative pain, thermal effects of the laser, postoperative back pain, spasm, and lack of visualization of the laser tip under fluoroscopy (20).…”
Section: Discussionsupporting
confidence: 87%
“…Vertebral endplate signal changes (VESC), also known as Modic changes [28], have been reported to be associated with low back pain (LBP) in people from the general [18], working [21,35], and clinical populations [2,5,6,13,43]. Seven out of ten studies included in a recent systematic review displayed significant positive associations between VESC and LBP, with odds ratios (OR) ranging from 2.0 to 20 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is considerable interest in the Holmium Yttrium-Aluminum-Garnet (Ho: YAG) laser, a solid-state laser that oscillates at a mid-infrared wavelength (2.1 mm) near the high light-absorption spectrum of water. Owing to its favorable features of affecting water-containing substances and excellent conductance through an optical fiber, Ho: YAG laser has already been applied to operations or interventions in the urinary tract [1], coronary artery [2], thoracic cavity [3], lumbar disc [4], nasal cavity [5], and skin [6]. From the physical point of view, three modes of applications can be distinguished on the basis of laser-tissue interaction and the nature of the surroundings.…”
Section: Introductionmentioning
confidence: 99%